Brain Gym Effectively Reduces Anxiety in School-and Preschool-Aged Children in Hospitals - Arbianingsih Arbianingsih; Huriati Huriati; Nur Hidayah; Syarifah Musnayni; Nuravia Afiifah; A. Adriana Amal (Faculty of Nursing Universitas Indonesia, 2021)
Hospitalization-induced anxiety in children can impede healing and lengthen hospitalization. As such, appropriate interventions are needed to reduce their anxiety during hospitalization. For example, brain exercise has been shown to reduce anxiety in children in diverse settings and developmental stages. This study was performed to compare the effect of brain exercise on anxiety in hospitalized school-and preschool-aged children. A pre-experimental pre/ posttest design was used, and 32 children were selected by consecutive sampling. Brain gym was given twice a day for 2 consecutive days. Data were collected from school-aged children by using a modified Zung Sel-Rating Anxiety Scale and Tailor Manifest Anxiety Scale and from preschoolers by utilizing a modified Hamilton Anxiety Rating Scale observation sheet. Wilcoxon test results showed that brain gyms were effective in reducing anxiety in school-aged children (p = 0.016) and preschoolers (p = 0.006). Movements during brain exercises could activate the neocortex and parasympathetic nerves that can ease psychic and physical tension. Therefore, brain gym can be an effective intervention to decrease anxiety in preschoolers and school-aged children. Abstrak Brain Gym Efektif Menurunkan Kecemasan Pada Anak Usia Sekolah dan Pra Sekolah di Rumah Sakit. Kecemasan akibat rawat inap pada anak dapat menghambat penyembuhan dan memperpanjang rawat inap. Dengan demikian, intervensi yang tepat diperlukan untuk mengurangi kecemasan mereka selama dirawat di rumah sakit. Misalnya, latihan otak telah terbukti mengurangi kecemasan pada anak-anak dalam berbagai pengaturan dan tahap perkembangan. Penelitian bertujuan untuk membandingkan pengaruh senam otak terhadap kecemasan pada anak usia sekolah dan prasekolah yang dirawat di rumah sakit. Penelitian menggunakan desain pre-eksperimen pre/posttest, dan 32 anak dipilih dengan sampel konsekutif. Senam otak diberikan dua kali sehari selama dua hari berturut-turut. Data yang dikumpulkan dari anak-anak usia sekolah menggunakan modifikasi Zung Sel-Rating Anxiety Scale dan Tailor Manifest Anxiety Scale, sedangkan data anak-anak prasekolah menggunakan lembar observasi modifikasi Hamilton Anxiety Rating Scale. Hasil uji Wilcoxon menunjukkan bahwa senam otak efektif menurunkan kecemasan pada anak usia sekolah (p = 0,016) dan anak prasekolah (p = 0,006). Gerakan pada saat senam otak dapat mengaktifkan neokorteks dan saraf parasimpatis yang dapat meredakan ketegangan psikis dan fisik. Oleh karena itu, senam otak dapat menjadi intervensi yang efektif untuk menurunkan kecemasan pada anak prasekolah dan usia sekolah. Kata Kunci: kecemasan, prasekolah, senam otak, usia sekolah